Explaining the Taliban’s Revival: Thomas Spragens’s Crisis Theory - Hossein Fattahi Ardakani (China Quarterly of International Strategic Studies)
The revival of the Taliban and their rapid domination of Afghanistan shocked the world. It is a response to the chronic historical, political and social crises of the Afghan society, which is still in geopolitical and strategic confusion and disorder. Using the analytical descriptive method, the present study attempts to answer the question related to the causes of the reemergence of the Taliban based on Thomas Spragens’ crisis theory. The research hypothesis states that the conflict between political actors and the creation of a political deadlock has caused successive crises and political, social and security disintegration in the society. Accepting the Taliban, the Afghan people seek to solve the crisis and restore, peace, stability, order and security for themselves and their descendants. It seems that the occupation of the country, nonimplementation of Sharia laws and spread of corruption are signs of a brewing crisis caused by the weakness of the central government, lack of nation-state agreement, the spread of ethnocentrism and overdependence on America. To address these challenges, Afghans increasingly resort to Jihad and the formation of an Islamic Emirate as a possible solution.